A Prospective Study of Loose Tissue Fragments in Non–Small Cell Lung Cancer Resection Specimens: An Alternative View to "Spread Through Air Spaces". (September 2017) - Blaauwgeers, Hans; Flieder, Douglas; Warth, Arne; Harms, Alexander; Monkhorst, Kim; Witte, Birgit; Thunnissen, Erik
Abstract : The World Health Organization Classification of Lung Tumors considers "Spread Through Air Spaces" a form of invasion in lung adenocarcinoma. The recently described spread of free-floating cell clusters during lung specimen sectioning, otherwise known as "Spread Through A Knife Surface, " represents an ex vivo artifact. The purpose of this study was to prospectively investigate the presence and frequency of these free-floating tumor cell clusters in surgically resected lung cancer specimens and their possible relation to gross examination procedures. A prospective, multi-institutional study of non–small cell lung cancer resection specimen was undertaken. At prosection the first cut was made with a clean knife; the second cut was made in a parallel plane to the first. Four tissue blocks were taken from upper and lower parts of first and second cuts. Hematoxylin and eosin–stained slides were examined for displaced benign and/or malignant tissue fragments. Forty-four resection specimens were studied. The mean number of tumor clusters for blocks 1 to 4 was 0.36, 1.44, 1.86, and 1.95, respectively, and for benign fragments was 0.11, 0.11, 0.13, and 0.25, respectively. Almost all cell clusters were intra-alveolar. Comparison of tumor cell clusters in block 1 with blocks 2 to 4 was significant with P -values (Friedman test for repeated measures 0.03) 0.031, 0.02, and 0.05, respectively. Overall 93% of the loose tissue fragments could be explained by mechanical forces associated with tissue handling. While the 2015 World Health Organization Classification of Lung Tumors recognizes Spread Through Air Spaces as a form of lung cancer invasion, such is debatable and in many instances likely represents mechanical artifact, including dissemination along the prosecting knife blade.